2004
DOI: 10.1002/ajmg.a.30181
|View full text |Cite
|
Sign up to set email alerts
|

A novel MSX1 mutation in hypodontia

Abstract: MSX1 mutations have been reported in four unrelated families with autosomal dominant tooth agenesis. In one family, some individuals also had cleft lip and/or palate. We have identified a novel MSX1 mutation (559 C --> T, resulting in Gln187Stop) in three individuals of one family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 18 publications
3
55
0
3
Order By: Relevance
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…These phenotypes include cleft palate, an absence of alveolar processes, and an arrest of tooth development at the bud stage, thus predicting the phenotype observed in humans carrying MSX1 mutations. Mutations in MSX1, a non-clustered homeobox protein, have been reported previously in families with autosomal dominant hypodontia (Vastardis et al 1996;van den Boogaard et al 2000;Jumlongras et al 2001;Lidral and Reising 2002;Jezewski et al 2003;De Muynck et al 2004). The present study presents the first mutation identified in a Pakistani family with autosomal recessive hypodontia with associated dental anomalies.…”
Section: Discussionmentioning
confidence: 89%
“…Environmental factors include radiation therapy, chemotherapeutic agents and use of thalidomide during pregnancy (Axrup et al 1966;Maguire et al 1987;Nasman et al 1997). In the majority of familial cases of hypodontia alone or its association with other anomalies, the mode of inheritance is autosomal dominant (Vastardis et al 1996;van den Boogaard et al 2000;Jumlongras et al 2001;Lidral and Reising 2002;Jezewski et al 2003;De Muynck et al 2004). An autosomal recessive model of hypodontia with associated anomalies was reported in a large family by Ahmad et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In humans, multiple MSX1 mutations have been identified in families exhibiting Mendelian inheritance of an oligodontia phenotype (either non-syndromic or syndromic). [3][4][5][6][7][8][9][10][11][12][13][14] However, MSX1 also clearly affects the common human oral cleft phenotypes, as demonstrated through multiple genetic studies. [15][16][17][18][19][20] Yet, in all but a single case report, 5 MSX1 apparently functions as a complex disease determinant for oral clefting.…”
Section: Introductionmentioning
confidence: 99%